Treatment options for acute myeloid leukemia patients aged <60 years - Visani, Giuseppe; Chiarucci, Martina; Paolasini, Sara; Loscocco, Federica; Isidori, Alessandro (Frontiers in Oncology, 2022)
Treatment of acute myeloid leukemia (AML) has changed over the last few years, after the discovery of new drugs selectively targeting AML blasts. Although 3/7 remains the standard of care for most AML patients, several new targeted agents (such as FLT3 inhibitors, CPX-351, gemtuzumab ozogamicin, BCL-2 inhibitor, oral azacitidine), either as single agents or combined with standard chemotherapy, are approaching clinical practice, starting a new era in AML management. Moreover, emerging evidence has demonstrated that high-risk AML patients might benefit from both allogeneic stem cells transplant and maintenance therapy, providing new opportunities, as well as new challenges, for treating clinicians. In this review, we summarize available data on first line therapy in young AML patient focusing on targeted therapies, integrating established practice with new evidence in the effort to outline the contours of a new therapeutic paradigm, that of a “total therapy”, which goes beyond obtaining complete remission.